Effects of Cigarette Prices on Intention to Quit, Quit Attempts, and Successful Cessation Among African American Smokers. Issue 4 (18th July 2018) - Keeler, Courtney; Max, Wendy; Yerger, Valerie B; Yao, Tingting; Wang, Yingning; Ong, Michael K; Sung, Hai-Yen
Abstract: Introduction: This study examined the effects of cigarette price on intention to quit, quit attempts, and successful cessation among African American smokers in the United States and explored whether price effects differed by income level and menthol use status. Price effects were further compared to White counterparts. Methods: We used pooled cross-sectional data from 2006 to 2007 and 2010 to 2011 Tobacco Use Supplements to the Current Population Survey to analyze 4213 African American recent active smokers. Three dependent variables were examined: any quit attempts in the past 12 months, successful cessation for at least 3 months, and intention to quit in the next 6 months. For each dependent variable, separate multiple logistic regression models were estimated to determine the impact of cigarette prices. Results: There was no indication that price was associated with quit attempts or successful cessation, but price was positively associated with increased odds of intending to quit among African American smokers ( p < .001). In contrast, prices were positively associated with intention to quit and quit attempts for White smokers. The association between price and intention to quit was significantly positive for African American low-income and menthol smokers but was not statistically significant for African American high-income and non-menthol smokers. There was no evidence of a price effect on quit attempts and successful cessation for each subgroup of African Americans. Conclusions: Tobacco tax policy alone may not be enough to increase quit attempts or successful cessation among African Americans. Community-based cessation programs tailored toward African American smokers, especially low-income menthol smokers, are needed. Implications: The results revealed that, among African American smokers, particularly among low-income and menthol smoking African American smokers, price appears to be positively associated with intention to quit; nevertheless, this deterrent effect does not appear to translate to actualized quit attempts or successful cessation. Increasing cigarette prices as a standalone policy may not be independently effective in increasing quit attempts and successful cessation within the African American community. Community-based cessation interventions tailored for African Americans are needed to help further translate desired cessation into actualized quit attempts.